High incidence supersonic similitude for planar wedge - Crasta, Asha; Khan, Sher Afghan (IJERA, 2012)
A similitude has been obtained for a planar wedge with attached bow shock at high incidence in supersonic flow. A strip theory in which flow at a span wise location is two dimensional developed by Ghosh is been used. This combines with the similitude to lead to a piston theory which gives closed form of solutions for unsteady derivatives in pitch. Substantially the same results as the theory of Liu and Hui are obtained with remarkable computational ease.